Case report: Conservative treatment of an intraperitoneal bladder rupture - Noah J. Sandel; Matthijs Duijn; Liselotte M.S. Boevé (Radiology Case Reports)
Bladder ruptures are uncommon but potentially life-threatening conditions, that necessitates prompt medical intervention. Urological trauma guidelines differentiate between intraperitoneal and extraperitoneal bladder ruptures. Intraperitoneal bladder ruptures typically require surgical repair, while extraperitoneal bladder ruptures are often treated conservatively. This case report presents a 25-year-old male patient with a significant intraperitoneal bladder rupture, successfully treated through conservative management. This case highlights the potential for nonoperative treatment in selected patients with intraperitoneal bladder injury, contributing to the evolving discussion on the management of urological trauma.